Study on unfrostered water content and strength characteristics of saturated sandstone during thawing process - Zuyong Li; Gengshe Yang; Baohui Wang; Jinlong Wang (Scientific Reports)
Abstract After the construction of the frozen wall of the vertical shaft is completed, it will undergo a long thawing process. Accumulation of damage under load may lead to the rupture of frozen walls and cause engineering accidents. The changes in mechanical properties during the thawing process of frozen rocks are key issues in controlling the stability of frozen walls. In view of the instability problem of the frozen wall of the vertical shaft, this article chooses the saturated sandstone of the Cretaceous system as the research object. Conduct triaxial compression tests under different temperature and confining pressure conditions. Obtain relevant parameters for analysis. And nuclear magnetic resonance technology was used to detect the changes in pore water content in saturated sandstone at different temperatures. The results indicate that: ① At room temperature, pore water mainly exists in the form of free water, while at low temperatures, pore water mainly exists in the form of adsorbed water. ② Compared with frozen soil, frozen rocks also exhibit significant supercooling phenomena. ③ According to the variation of unfrozen water content in saturated sandstone at different temperatures, it can be divided into three stages: freezing cessation (− 20 ℃ ~ − 6 °C), stable freezing (− 6 °C ~ − 2 °C), and rapid freezing (-2 ℃ ~ 20 ℃). ④ As the temperature increases, the closure level of saturated sandstone gradually increases, while the initiation and expansion levels gradually decrease. ⑤ There is an exponential relationship between the unfrozen water content and the peak strength of saturated sandstone, with a good correlation. And show the same trend of change under different confining pressures. The research results can provide theoretical support and experimental basis for evaluating the instability and failure induced by thawing of frozen walls.